Politeness Strategies in Comic Strip Dialogues of Junior High School English Textbooks - Komang Satria Wirasa (LITERA : Jurnal Bahasa Dan Sastra, 2025)
Within the framework of Kurikulum Merdeka, English language instruction emphasizes not only the acquisition of linguistic structures but also the pragmatic use of language across diverse social and cultural contexts. Comic strips, as part of the learning materials, offer authentic language interactions that reflect everyday communication and provide exposure to various politeness strategies. This study employed a qualitative approach with content analysis as the method to examine 164 utterances found in the comic strips. The utterances were classified using Brown and Levinson’s (1987) theory, which identifies four types of politeness strategies: bald on-record, positive politeness, negative politeness, and off-record. The findings show that bald on-record strategy was the most frequently used (93 instances), followed by positive politeness (70 instances). Negative politeness was absent, and off-record occurred only once. The predominance of direct strategies is likely attributed to the informal nature of peer-to-peer interactions, where minimal social distance reduces the need for indirectness. These results suggest that comic strips can serve as effective pedagogical tools for fostering learners’ pragmatic competence, particularly in the domain of politeness. The study provides pedagogical implications for educators and material developers in designing instructional resources that integrate both linguistic and pragmatic dimensions of language learning.